Treatment of combined sewer overflow using retention treatment basin assisted with polymer chemical coagulation - El-Gendy, Ahmed S (Water environment research : a research publication of the Water Environment Federation, 2008)
Pilot plant experiments were conducted to examine the performance of a retention treatment basin (RTB) with chemical coagulation using a cationic polymer in the treatment of combined sewer overflow (CSO) for the City of Windsor, Ontario, Canada. The pilot plant was operated at surface overflow rates (SORs) up to 1370 m3/m2 x d. This study demonstrated that the use of polymer coagulation improved settling characteristics of solids, and allowed the SOR in the RTB to be increased significantly. An optimum polymer dosage to achieve the discharge standards of CSO was determined from the experimental runs. The effluent quality met the Ontario Ministry of the Environment Procedure F5-5 in terms of 5-day biochemical oxygen demand and total suspended solids removals. A flushing box was successfully tested for flushing the collected floatables and sludge from the bottom of the RTB after storm events